Process Parameters Optimization For Bioremediation Of Crude Oil In Contaminated Coastal Sediments - Mohajeri, Leila (2010)
Crude oil causes a variety of risks when released into the environment. Biodegradation of hydrocarbon compounds is one of the most important processes for clean-up of the environment. One of the current knowledge gaps is the suitable concentration of weathered crude oil (WCO) in coastal sediment for selection of bioremediation as a clean-up option. In the first layout of this study, biodegradation of three different concentrations of synthetic weathered crude oil was investigated at laboratory scale. Natural attenuation, biostimulation and bioaugmentation were determined and compared at 3, 30, 60 g oil per kg dry sediment. Samples were collected from the Butterworth channel and acclimatized indigenous microorganisms were used. Total petroleum hydrocarbons (TPHs) were measured by gravimetric method on days 0, 7, 14, 28, 50, 70 and 90. Highest removal of 73.8 % was observed in bioaugmentation experiments for oil concentration of 30 g/kg dry soil while natural attenuation process removed 15.5 % of TPHs in 90 days. Removal by natural attenuation was slow; however, addition of nutrient increased its removal compared to non-stimulated reactors in all three oil concentrations. Bioremediation during 70 days reached the maximum value and no significant further decrease was observed up to 90 days. In the second part, TPHs and selected n-alkanes were measured at 0, 6, 14, 25, 40 and 60 days after introducing WCO to coastal sediment samples by gravimetric method and gas chromatography. Experiments were designed by response surface methodology (RSM) and central composite design (CCD). Initial oil concentration, microorganism, nitrogen and phosphorus concentrations were used as independent variables (factors). TPHs removal and n-alkanes removal were investigated separately as dependent variables (response). For each test a quadratic polynomial model was generated.